2014
DOI: 10.1136/annrheumdis-2013-204909
|View full text |Cite
|
Sign up to set email alerts
|

PXKlocus in systemic lupus erythematosus: fine mapping and functional analysis reveals novel susceptibility geneABHD6

Abstract: These results confirm the genetic association of the locus 3p14.3 with SLE in Europeans and point to the ABHD6 and not PXK, as the major susceptibility gene in the region. We suggest a pathogenic mechanism mediated by the upregulation of ABHD6 in individuals carrying the SLE-risk variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
(46 reference statements)
0
18
2
Order By: Relevance
“…Higher expression of ABHD6 in PBMCs defines an SLE endophenotype An overexpression of ABHD6 in SLE patients was suggested in the previous study, which first identified polymorphisms of ABHD6 as the PXK-locus associated predisposition for SLE (7). To examine this, we recruited a cohort of SLE patients and checked the expression of ABHD6 in PBMCs and found that there is significant overexpression of ABHD6 in SLE patients (n = 90, female = 86, male = 4), as compared with healthy controls (n = 76, female = 32, male = 44) ( Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Higher expression of ABHD6 in PBMCs defines an SLE endophenotype An overexpression of ABHD6 in SLE patients was suggested in the previous study, which first identified polymorphisms of ABHD6 as the PXK-locus associated predisposition for SLE (7). To examine this, we recruited a cohort of SLE patients and checked the expression of ABHD6 in PBMCs and found that there is significant overexpression of ABHD6 in SLE patients (n = 90, female = 86, male = 4), as compared with healthy controls (n = 76, female = 32, male = 44) ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Genome-wide association studies have linked multiple genomic loci with SLE susceptibility, although direct pathogenetic role of very few of them have been reported, apart from the genes directly linked to induction and response of type I IFNs (5,6). A recent genome-wide association study had reported association of a novel gene, a/b-hydrolase domain-containing 6 (ABHD6), with SLE susceptibility (7).…”
Section: Cutting Edge: Dysregulated Endocannabinoid-rheostat For Plasmentioning
confidence: 99%
“…Refining candidate genes in IBD and autoimmune/autoinflammatory disease-associated risk loci has advanced by exome-sequencing studies, fine mapping of high confidence risk loci, and eQTL analysis (27, 5961). However, the major integrative analyses with eQTLs, such as those for rheumatoid arthritis (61), systemic lupus erythematosus (62), and multiple sclerosis (63), have used eQTLs defined in peripheral blood (64) or immune cell subsets (63, 65). eQTL mapping in neutrophils (66, 67), monocytes (10), and dendritic cells (68) has expanded by comparing resting cells with cells after immune stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of ABHD6 also increases 2-AG signaling through CB1 receptors in the CNS (77, 78). ABHD6 also has significant functions outside of the CNS e.g., (79, 80), which will complicate the application of ABHD6-based therapies to CNS disorders. ABHD12 is the other major hydrolytic enzyme suggested to be involved in the hydrolysis of 2-AG in brain.…”
Section: Endocannabinoid Degradationmentioning
confidence: 99%